HCN ice in Titan's high-altitude southern polar cloud. - de Kok, R; Teanby, N; Maltagliati, L; Irwin, P; Vinatier, S (2014)
Titan's middle atmosphere is currently experiencing a rapid change of season after northern spring arrived in 2009 (refs 1, 2). A large cloud was observed for the first time above Titan's southern pole in May 2012, at an altitude of 300 kilometres. A temperature maximum was previously observed there, and condensation was not expected for any of Titan's atmospheric gases. Here we report that this cloud is composed of micrometre-sized particles of frozen hydrogen cyanide (HCN ice). The presence of HCN particles at this altitude, together with temperature determinations from mid-infrared observations, indicate a dramatic cooling of Titan's atmosphere inside the winter polar vortex in early 2012. Such cooling is in contrast to previously measured high-altitude warming in the polar vortex, and temperatures are a hundred degrees colder than predicted by circulation models. These results show that post-equinox cooling at the winter pole of Titan is much more efficient than previously thought.